UJI DAYA ANTIINFLAMASI SERBUK CACING TANAH (Lumbricus rubellus) DENGAN METODE UDEMA TERINDUKSI KARAGENIN PADA TELAPAK KAKI TIKUS - , SHOFIATININGSIH; , Arief Rahman Hakim M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Inflammation is a normal response of the body protection. But if it happens excessively, inflammation can damage tissue, so that the anti-inflammatory drug needed to overcome it. Most inflammatory treatment using non-steroidal anti-inflammatory drugs (NSAIDs). However, side effects occur of NSAIDs used, like gastric mucosa , intestine, liver, and kidneys disorders. Lumbricus rubellus empirically used as an anti-inflammatory. This study aimed to investigate the anti-inflammatory activity of Lumbricus rubellus powder and effect of the dose variation on the anti-inflammatory activities is generated, using the test method karagenin induced edema in the feet of rats. Wistar male rats used thirty-tails. Randomly divided into five groups of test, control 0.5% CMC Na, pottasium diclofenac as comparator 9 mg/kg, and three variations of doses SLR, 90, 180, and 270 mg/kg in p.o administration. As an inducer of inflammation used karagenin 1%. Rat foot volume measurements performed immediately after subplantar injection of 0.1 ml karagenin 1%, using plethysmometer. The volume of rat feet measured every 30 minutes for 6 hours. Further statistical analysis ANOVA on AUC and % DAI values. The test results showed the SLR has anti-inflammatory activity because it can reduce the volume of rat foot edema. Anti-inflammatory activities of pottasium diclofenac 9 mg/kg, SLR dose 90, 180, and 270 mg/kg respectively were 42.83+8.75